ANALISIS SISTEM PENILAIAN KOMPETENSI PEMEGANG JABATAN DENGAN KOMPETENSI KERJA DI KELUARGA JABATAN UMUM PADA PT JASA MARGA (PERSERO) - Ismulyana Djan; Ida Juraida (Jurnal Ilmiah Binaniaga, 2007)
The purpose of the research was to know whether the implementation of Human resource competency at Jasa Marga (Ltd) has been run well in terms of employee recruitment. The two variables being compared in this study were the competency of the employees who hold positions and the work competency itself. The study focuses on analyzing the existing employees competency with the needed job requirements.  The research used descriptive method with qualitative approach by interviewing related parties and conducting a field observation concerning the problem being researched. From measuring competency of the employees who hold positions at Jasa Marga (Ltd) it was found that there were still a few employees whose qualification were below the job requirements. It was proposed that Jasa Marga (Ltd) should continuously increase the quality of the human resources through development training in short term and long-term programs in order to fulfill the predetermined job requirements. The application of the employees competency training should be conducted interactively to produce professional and transparent human resource because it function as initial filter from the early employees recruitment and selection programs.